Analisis Tingkat Loyalitas Konsumen Generasi Z terhadap Marketplace di Indonesia Menggunakan Metode NPS (Net Promoter Score) - Tarigan, Nerys Lourensius L.; Wijaya, Petra Surya Mega; Wahyuni, Yuyun; Sulistyowati, Eny (Jurnal Manajemen Strategis: Jurnal Mantra, 2024)
Research on consumer loyalty, especially in generation Z, is the last interesting research both in Indonesia and other countries. Loyalty is an important part of the company because it becomes a positive and very profitable behavior for the company. The purpose of this study is to measure the level of consumer loyalty to generation Z in Indonesia. The object of the study took seven marketplace sites that are often used by generation Z in Indonesia. The marketplaces are (1) Shopee, (2) Lazada, (3) Tokopedia, (4) Zalora, (5) Bukalapak, (6) Blibli.com, and (7) Instagram. The method used to measure the level of consumer loyalty is NPS (Net Promoter Score). Surveys use random sampling. A total of 153 respondents gave answers using google forms. The results showed that there were only 2 marketplaces that were included in the loyal category, namely Shopee, and Tokopedia, while the rest, namely Lazada, Zalora, Bukalapak, Blibli.com, and Instagram, were included in the non-loyal category.